Novel type of red-shifted chlorophyll a antenna complex from Chromera velia. I. Physiological relevance and functional connection to photosystems - Kotabová, Eva; Jarešová, Jana; Kaňa, Radek; Sobotka, Roman; Bína, David; Prášil, Ondřej (Biochimica et biophysica acta, 2014)
Chromera velia is an alveolate alga associated with scleractinian corals. Here we present detailed work on chromatic adaptation in C. velia cultured under either blue or red light. Growth of C. velia under red light induced the accumulation of a light harvesting antenna complex exhibiting unusual spectroscopic properties with red-shifted absorption and atypical 710nm fluorescence emission at room temperature. Due to these characteristic features the complex was designated "Red-shifted Chromera light harvesting complex" (Red-CLH complex). Its detailed biochemical survey is described in the accompanying paper (Bina et al. 2013, this issue). Here, we show that the accumulation of Red-CLH complex under red light represents a slow acclimation process (days) that is reversible with much faster kinetics (hours) under blue light. This chromatic adaptation allows C. velia to maintain all important parameters of photosynthesis constant under both light colors. We further demonstrated that the C. velia Red-CLH complex is assembled from a 17kDa antenna protein and is functionally connected to photosystem II as it shows variability of chlorophyll fluorescence. Red-CLH also serves as an additional locus for non-photochemical quenching. Although overall rates of oxygen evolution and carbon fixation were similar for both blue and red light conditions, the presence of Red-CLH in C. velia cells increases the light harvesting potential of photosystem II, which manifested as a doubled oxygen evolution rate at illumination above 695nm. This data demonstrates a remarkable long-term remodeling of C. velia light-harvesting system according to light quality and suggests physiological significance of 'red' antenna complexes.
Keywords: chlorofyl; fyziologická adaptace; Light-harvesting complex; Photosystem II; kinetika; Electrophoresis, Polyacrylamide Gel; Chromatic adaptation; Kinetics; Chlorophyll A; Photosynthetic Reaction Center Complex Proteins; Photosynthesis; Non-photochemical quenching; 2D gelová elektroforéza; Chromera velia; fotosyntetická reakční centra (proteinové komplexy); Electrophoresis, Gel, Two-Dimensional; mikrořasy; Microalgae; Spectrometry, Fluorescence; fluorescenční spektrometrie; Red-shifted chlorophyll; elektroforéza v polyakrylamidovém gelu; chlorofyl a; Chlorophyll; Adaptation, Physiological; fotosyntéza